Two Adolescents : agostino and disobedience - Moravia, Alberto (Great Britain : Penguinn Books, 1950)
Explores the complex minds of two youths awakening to sensuality with all the exquisite pleasure and intense pain of first discovery. From Agostino, the adoring son of a capricious widow, to Luca, a gangly boy confused by his own changing desires
Keywords: Novel; Fiction; Psychology